2009
DOI: 10.1007/s00402-009-1027-1
|View full text |Cite
|
Sign up to set email alerts
|

Minimal invasive fixation of proximal humeral fractures with an intramedullary nail: good results in elderly patients

Abstract: Minimally invasive fixation of displaced 2-part and 3-part humeral fractures in an elderly population shows satisfactory to excellent results in 80% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
1
15
1
5
Order By: Relevance
“…It is important to note that, despite our re‐operation rate, our other complication rates are better than most published series. Our re‐operation rate of 21.3% compares to values of 17.2% to 38.9% [23,25,32]. Impingement has been reported in 1.9% to 38.9% of patients [23,26,27,32], greater tuberosity non‐union or malunion in 3.7% to 55.6% [23–27], screw back‐out in 3.4% to 7.4% [25,27,30], avascular necrosis (AVN) in 2.8% to 3.7% [25,26,30], intra‐articular screw protrusion in 7.4% to 17.6% [26,32], iatrogenic fracture in 17.2% [25], stiffness in 3.7% [30], infection in 0.9% to 8.8% [26,27,32] and transient radial nerve palsy in 4.2% [24].…”
Section: Discussionmentioning
confidence: 94%
“…It is important to note that, despite our re‐operation rate, our other complication rates are better than most published series. Our re‐operation rate of 21.3% compares to values of 17.2% to 38.9% [23,25,32]. Impingement has been reported in 1.9% to 38.9% of patients [23,26,27,32], greater tuberosity non‐union or malunion in 3.7% to 55.6% [23–27], screw back‐out in 3.4% to 7.4% [25,27,30], avascular necrosis (AVN) in 2.8% to 3.7% [25,26,30], intra‐articular screw protrusion in 7.4% to 17.6% [26,32], iatrogenic fracture in 17.2% [25], stiffness in 3.7% [30], infection in 0.9% to 8.8% [26,27,32] and transient radial nerve palsy in 4.2% [24].…”
Section: Discussionmentioning
confidence: 94%
“…Cuny et al [15] reported ten cases of revision surgery (15 %) for mechanical problems with the Telegraph nail and six cases of secondary tuberosity displacement. Sosef et al [16] in a series of 33 patients treated by Polaris nail, most of them for 2-PF, report 18 % revisions for mechanical problems; whereas Nolan et al [17], in a series of 18 patients with 2-and 3-PFs, with an average age of 71 years treated with Polaris nail, reported seven cases necessitating revision surgery (39 %) for mechanical problems.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent clinical series on IM nailing using specially designed nails have reported high union rates and satisfactory functional outcomes of treatment of proximal humeral fractures 1315). However, the use of IM nails for pathological proximal humeral fractures has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have been published on IM nail fixation techniques for proximal humerus fractures using devices that provide screw stabilization of the humeral head and tuberosity. They provide rigid fixation without extensive soft-tissue dissection 1213). In our patients, we applied an IM nailing technique, interlocking IM nailing with additional augmentation of the skeletal defect with bone cement, for pathological fractures of the proximal humerus.…”
mentioning
confidence: 99%